Llengua literària i actitud política en Teodor Llorente. A propòsit de «Cartes de soldat» i «Pro patria» - Ferrando, Antoni (Caplletra. Revista Internacional de Filologia, 2015)
Llorente, in spite of his political and literary conservatism and his unitary beliefs concerning language, employed several linguistic registers in order to maintain his position as the intellectual leader of the Renaixença in Valencia.